PENGARUH PENYULUHAN PENCEGAHAN COVID-19 TERHADAP PENGETAHUAN DAN SIKAP MASYARAKAT DI KELURAHAN WAJO KOTA BAU-BAU - Ferryanti Mery; Asriati Asriati; Adius Kusnan (NHM PRESS, 2021)
Background. Coronavirus is a family virus that infects animals and humans so that it causes a pandemic and needs to be prevented. Purpose. This study aims to determine the effect of COVID-19 prevention counseling on the knowledge and attitudes of the Wajo Regency in Baubau City. Method. This study used a quasi-experimental one group pretest-posttest design study, counseling was provided by means of indirect communication which was carried out in Wajo Regency, Baubau City. The number of samples in this study were 40 patients. The data were collected using primary data in the form of a questionnaire in accordance with the inclusion criteria. The data were processed using paired t test analysis. Result. The results of the research on knowledge before extension were compared to after 3 days of extension, the value of 1.950 was obtained with a value of P = 0.000 (significance). Then after 6 days of counseling the value was 3.975 with a value of P = 0.000 (significance). The results of the study on attitudes before counseling were compared with those after 3 days of extension, which resulted in 2.050 with a value of P = 0.000 (significance). Then after 6 days of counseling the value was 3,950 with a value of P = 0,000 (significance). Conclusions. Based on the results of research and discussion, the conclusion of this study is that there is an effect of COVID-19 prevention counseling on the knowledge and attitudes of the community in Wajo Regency, Bau-bau City.